Polarization Angle Effect on High-Order Harmonic Generation in an Inhomogeneous Two-Color Laser Field - Stephen Maina Njoroge (Department of Physics, Sebelas Maret University, 2025)
Theoretical investigation of the effect of the polarization angle on high-order harmonic generation in an inhomogeneous two-color field is reported. The results show that the use of two-color fields greatly enhanced the harmonic cutoff point in comparison with the one-color field from 70th to 90th orders in a homogeneous field. In addition, the introduction of an inhomogeneity parameter of 0.003 generated a broad supercontinuum of approximately 270 orders. However, an increase in the polarization angle adversely affected the harmonic cutoff.